Glyphosate and its formulations Roundup Bioflow and RangerPro alter bacterial and fungal community composition in the rat caecum microbiome - Mesnage, Robin; Panzacchi, Simona; Bourne, Emma; Mein, Charles A.; Perry, Melissa J.; Hu, Jianzhong; Chen, Jia; Mandrioli, Daniele; Belpoggi, Fiorella; Antoniou, Michael N. (Frontiers in Microbiology, 2022)
Potential health consequences of glyphosate-induced gut microbiome alterations have become a matter of intense interest and concern. As part of a study investigating toxicity, carcinogenicity and multigenerational effects of glyphosate and its commercial herbicide formulations, we assessed changes in bacterial and fungal populations in the caecum of rats exposed prenatally until adulthood (13 weeks after weaning) to three doses of glyphosate (0.5, 5, 50 mg/kg body weight/day), or to the herbicide formulations Roundup Bioflow and RangerPro at the same glyphosate-equivalent doses. Fungal and bacterial diversity were altered by Bioflow and RangerPro in a dose-dependent manner, whilst glyphosate alone significantly altered only bacterial diversity. At a taxa level, a reduction in Bacteroidota abundance, marked by changes in Alloprevotella, Prevotella and Prevotellaceae UCG-003 was concomitant with increases in Firmicutes (e.g., Romboutsia, Dubosiella, Eubacterium brachy group or Christensenellaceae) and Actinobacteria (e.g., Enterorhabdus, Adlercreutzia, or Asaccharobacter). Treponema and Mycoplasma were also reduced by the treatments. Fungal composition analysis showed the abundance of the commensal Ascomycota Kazachstania was reduced whilst that of Gibberella, Penicillium, Claviceps, Cornuvesica, Candida, Trichoderma and Sarocladium were increased by Bioflow and RangerPro, but not glyphosate. Our data show that glyphosate and especially its formulations RangerPro and Roundup Bioflow caused profound changes in rat caecum microbiome composition by affecting the fitness of major commensals, which in turn reduced competition and allowed opportunistic fungi to proliferate. This further indicates that changes in gut microbiome composition might influence the long-term toxicity, carcinogenicity and multigenerational effects of glyphosate-based herbicides.